Hiijrah: Islamic E-Commerce Disurpted Strategy - Maika, M. Ruslianor; Kautsar, Irwan Alnarus (Economica: Jurnal Ekonomi Islam, 2019)
The aims of this research is to find an Islamic eCommerce disrupted strategy using 5C model. Our methodologies is a qualitative descriptive to evaluate and describe aspects of innovation based on 5C model. We propose a systematic approach to identify disruptive strategies of Prophet Muhammad displacing the big incumbent market and also provide commercialize the strategy for developing and implementing Islamic Commerce to be electronics. Hijrah is the best disruptive approach that was proven by Prophet Muhammad (PBUH) with the closing of the Bani Qainuqa market. He implemented 4C model commerce, collaboration, communication, connection, and only computation that He can?t. The state art of this research are the customers not only ?go shopping?, but literally are shopping. While the sellers not only ?go selling? but Hijrah with the great intention. It is not only about adopting technology but also as a disrupted strategy.Tujuan dari penelitian ini adalah untuk menemukan sebuah strategi diruptif eCommerce Islam menggunakan model 5C (Commerce, Collaboration, Communication, Connection, and Computing). Metodologi yang kami gunakan adalah deskriptif kualitatif, untuk mengevaluasi dan menggambarkan aspek inovasi berdasarkan model 5C. Kami menawarkan sebuah pendekatan sistematik untuk mengenali strategi disruptif Nabi Muhammad dalam menggusur pasar besar milik petahana dan juga menyediakan strategi komersil dalam mengembangkan dan menerapkan perdagangan Islam secara elektronik (Islamic e-commerce). Hijrah adalah pendekatan distruptif terbaik yang pernah dibuktikan oleh Nabi Muhammad Saw dengan menutup pasar Bani Qainuqa. Nabi Muhammad Saw menjalankan model 4C yaitu perdagangan, kolaborasi, komunikasi, koneksi, dan hanya komputasi yang tidak dapat dilakukan. Hasil temuan-temuannya menunjukan bahwa pelanggan tidak hanya untuk ?berbelanja?, tapi ada tujuan lain memahami kaidah Ilmu sebelum amal dalam berbelanja. Sedangkan penjual tidak sekedar ?berjualan? namun berhijrah dengan nilai yang lebih agung. Hal ini tidak hanya perihal penggunaan teknologi tapi juga sebagai strategi disruptif.